2021
DOI: 10.1029/2021wr029679
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impacts of Source Condition Uncertainties on Far‐Field Brine Leakage Plume Predictions in Geologic Storage of CO2: Integrating Intermediate‐Scale Laboratory Testing With Numerical Modeling

Abstract: Natural fissures/faults or pressure‐induced fractures in the caprock confining injected CO2 have been identified as a potential leakage pathways of far‐field native brine contaminating underground sources of drinking water. Developing models to simulate brine propagation through the overlaying formations and aquifers is essential to conduct reliable pre‐ and post‐risk assessments for site selection and operation, respectively. One of the primary challenges of performing such simulations is lack of adequate inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(49 citation statements)
references
References 128 publications
(199 reference statements)
4
45
0
Order By: Relevance
“…Concentration data was generated through chemically analyzing the collected aqueous samples from the selected septa-ports by the OD framework using an ion chromatography (IC) system (Dionex Aquion combined with autosampler Dionex As-Dv). More details of the sampling approach used in this study can be found in Askar et al (2021). The hydraulic heads were measured using the manometers selected by the OD framework as well, twice a day.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Concentration data was generated through chemically analyzing the collected aqueous samples from the selected septa-ports by the OD framework using an ion chromatography (IC) system (Dionex Aquion combined with autosampler Dionex As-Dv). More details of the sampling approach used in this study can be found in Askar et al (2021). The hydraulic heads were measured using the manometers selected by the OD framework as well, twice a day.…”
Section: Methodsmentioning
confidence: 99%
“…FEFLOW solves the groundwater flow and transport equations using a continuous finite-element scheme (Diersch, 2014). It is worth mentioning that a FEFLOW-based model was validated by Askar et al (2021) using experimental data for its ability to capture the migration of a bromide plume under multi-dimensional complex flow fields in a system with three geologic zones similar to this study. The solution domain of the base-models was discretized with a high-resolution mesh (∼190,000 triangular elements) to represent the heterogenous sand packing of Zone 3 and the sand layers of Zone 2.…”
Section: Model Setup and Parametrizationmentioning
confidence: 97%
See 3 more Smart Citations